Disfunção sexual, aborto, diversidade sexual, comportamento sexual de risco e crime em uma amostra de usuários de drogas não injetáveis - Reis, Alessandra Elena Diehl Branco dos [UNIFESP] (2016)
Objective: To evaluate the prevalence of sexual risky behaviors, abortion, sexual dysfunction, crime and associated factors in a sample of alcohol and non-injected drugs users admitted to a specialized unit for treatment of chemical dependence. Material and Methods: this was a cross-sectional study, using a structured instrument applied in consecutive admissions, containing sociodemographic data, characteristics related to sexual behavior and scales to assess the presence of sexual dysfunction symptoms, level of dependence of psychoactive substances, impulsivity, and screening of sex addiction. Results: a sample of 616 patients, 82.5% men, 51.9% were single, 54.5% white, in 71.4% the family monthly income is 1 to 3 minimum wages, 47.3% have less than 8 years of schooling, in 49.4% crack was the drug of choice. Sexual dysfunction was common in both men (37.2%) and women (34.2%) with similar prevalence rates betwen both sexes. Higher levels of psychoactive dependence made it more common to have sexual dysfunctions. Especially, high level of nicotine dependence was associated with sexual dysfunction in women who use psychoactive substances, increasing by about 2 times the odds of sexual dysfunctions. In women, there were no statistical differences between the prevalence of sexual dysfunction investigated using a standardized scale and a single direct question about difficulties / dysfunctions. Among men, premature ejaculation (53.2%) was the most common sexual dysfunction and 89.8% of those who have sexual complaints never sought medical help. Many sexual behaviors of high vulnerability, such as exchanging sex for drugs, sex with prostitutes, and multiple sexual partners were associated with the level of psychoactive substance dependence, increasing the chances of sexual risky behavior. Alcohol and cocaine were the drugs of choice that were more associated with sexual behaviors of high vulnerability and not crack, as initially expected in the present study. Half of crack users tend not to use condoms, especially men. The three main reasons reported for not using condoms were the fact of having a stable partner, belief in the decrease of sensitivity and being too excited to put on a condom. In both sexes, no condom use was associated with more severe levels of dependence on substances. In this sample, crime history (32%) was associated with several sexual behaviors and severity of psychoactive substances. The prevalence of induced abortion in this 339 sample was 26.8% and was significantly associated with dependence levels of psychoactive substances and sexual risk behavior. The tabacco use is positively associated to sexual orientation. Although 23.9% were screenined as possible sex dependents.Conclusion: Psychoactive substance dependents have various sexual behaviors of vulnerability and high prevalence of sexual dysfunction and crimes related to level of dependence and problems with alcohol and other drugs.